18F labeling of arenes. - Tredwell, M; Gouverneur, V (2012)
Molecular imaging has witnessed an upsurge in growth, with positron emission tomography leading the way. This trend has encouraged numerous synthetic chemists to enter the field of (18) F-radiochemistry and provide generic solutions to address the well-recognized challenges of late-stage fluorination. This Minireview focuses on recent developments in the (18)F-labeling of aromatic substrates.